Trabalho docente na educação à distância: a UFPA como expressão do fenômeno - MONTE, Emerson Duarte (Universidade Federal do Pará, 2012)
This study main aims at examining the teachers’ work in undergraduate courses at a distance, taking as example the course in Mathematics in the distance at the Universidade Federal do Pará, in the context of the policy of expansion of higher education through for the distance mode. The study uses official documents that deal with the policy of expanding higher education through distance education, the federal laws and documents concerning the policy of expanding the distance mode in the Universidade Federal do Pará, as well as interviews with the former and current coordinators of the course in question. We started from the premise that the present form of capitalist organization of production demand workers with minimal training - basic education - and, for this it is necessary to expand enrollments in higher education to ensure the universalization of basic education. Indications the collective bodies of the capital, such as the World Bank and United Nations Educational, Scientific and Cultural Organization, with regarding the policy of expanding higher education emphasize the use of new technologies the information and communication as a tool useful for the development of courses in the distance mode and thus more efficient than classroom courses, because they are less expensive, flexible in the time and space and wide dissemination. In this context, the expansion of higher education in Brazil is through distance education, especially for the private institutions. Was found that one of the central actors in higher education is the teacher worker that in the past two decades, lives the expansion of the precariousness and the intensification of work. The study indicates widespread development of undergraduate courses in distance mode with rates higher than those observed in the presence education, in the both public and private institutions. With regard to teacher worker in the distance mode, the studies point to an enhancement of precariousness and the intensification of teachers' work, but despite that, this mode of education is still on the rise. In the case of ongoing analysis has revealed the presence of particular elements of precariousness and the intensification of teachers' work, such as increased workload without increasing pay, accumulation of activities by teachers, lack of training policy for specific of the teachers, little production, the teacher of the course, teaching materials specific to distance learning courses.